2011
DOI: 10.1371/journal.pone.0023971
|View full text |Cite
|
Sign up to set email alerts
|

Functional Dissection of the TBK1 Molecular Network

Abstract: TANK-binding kinase 1 (TBK1) and inducible IκB-kinase (IKK-i) are central regulators of type-I interferon induction. They are associated with three adaptor proteins called TANK, Sintbad (or TBKBP1) and NAP1 (or TBKBP2, AZI2) whose functional relationship to TBK1 and IKK-i is poorly understood. We performed a systematic affinity purification–mass spectrometry approach to derive a comprehensive TBK1/IKK-i molecular network. The most salient feature of the network is the mutual exclusive interaction of the adapto… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
133
2
1

Year Published

2013
2013
2020
2020

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 119 publications
(144 citation statements)
references
References 45 publications
8
133
2
1
Order By: Relevance
“…We have previously shown that TBK1 physically associates with those intracellular Salmonella that are positive for the TBK1 adaptor proteins Nap1 and Sintbad and the autophagy cargo receptor NDP52 (Thurston et al , 2009). To test whether the function of TBK1 in anti‐bacterial autophagy requires interactions with its adaptor proteins we truncated TBK1 at its C‐terminus (TBK1 N685 hereafter referred to as TBK1 ΔC ), thereby generating a molecule deficient in binding to all its known adaptors, that is Nap1, Sintbad, Tank, and optineurin (Fig EV1B) (Goncalves et al , 2011), while maintaining kinase activity as indicated by the activation of an ISRE reporter (Fig EV1C). Complementation of Tbk1 −/− MEFS with TBK1 ΔC failed to restrict proliferation of S .…”
Section: Resultsmentioning
confidence: 99%
“…We have previously shown that TBK1 physically associates with those intracellular Salmonella that are positive for the TBK1 adaptor proteins Nap1 and Sintbad and the autophagy cargo receptor NDP52 (Thurston et al , 2009). To test whether the function of TBK1 in anti‐bacterial autophagy requires interactions with its adaptor proteins we truncated TBK1 at its C‐terminus (TBK1 N685 hereafter referred to as TBK1 ΔC ), thereby generating a molecule deficient in binding to all its known adaptors, that is Nap1, Sintbad, Tank, and optineurin (Fig EV1B) (Goncalves et al , 2011), while maintaining kinase activity as indicated by the activation of an ISRE reporter (Fig EV1C). Complementation of Tbk1 −/− MEFS with TBK1 ΔC failed to restrict proliferation of S .…”
Section: Resultsmentioning
confidence: 99%
“…It forms a family with proteins harboring coiled-coil domains and a TBK1-binding domain, namely, TANK and TBKBP1 (23). AZI2 interacts with TBK1 and IKK-i, and was shown to be involved in IFN-b induction in response to TLR and RLR stimulation (32,33). AZI2 was also found to be involved in the activation of IRF3 in response to poly(I:C) (25).…”
Section: Discussionmentioning
confidence: 99%
“…6E) (32,33). Although expression of the coiled-coil domains of AZI2 (1-158) failed to rescue the defect in DC differentiation in AZI2 -/-BM cells, expression of AZI2 (1-270) containing the TBK1-binding domain greatly increased the proportion of CD11c + cells (Fig.…”
Section: Azi2 Is Required For the Proliferation Of Gm-dcs Via Tbk1mentioning
confidence: 94%
“…S1). This observation may underlie the ability of IKK␤ and IKK␣ to form homo-or heterodimer complexes (33) and the significant difference in dimerization interfaces between IKKB and TBK1 (6,30,39).…”
Section: Analysis Of Protein Constructs and Crystallization-twomentioning
confidence: 99%